Indigenous Knowledge of Apatani Tribe of Cultivation and Utilization of Runner Bamboo (Phyllostachys bambusoides Gamble) in Arunachal Pradesh - Melkania, N. P. (Indian Forester, 2008)
Bamboos are potential bioresources of tangible and intangible values for humankind. Tropical and sub-tropical Indian forests and agrarian ecosystems harbour great species diversity of bamboos. Majority of bamboo species find favourable niche in the North-Eastern Region of the country. Among these, Phyllostachys bambusoides Gamble is confined only to Apatani plateau in Lower Subansiri District of Arunachal Pradesh, thus called commonly 'Apatani' bamboo. It is strictly a cultivated bamboo either grown as sole crop on land adjacent to cultivation fields and/or in association of Pinus excelsa. The present contribution documents, based on field surveys, the indigenous knowledge of Apatanis of cultivation and utilization of P. bambusoides. The information will be useful for development workers and extension services involved in bamboo development and natural resource management.